Influência de personagens infantis sobre escolhas alimentares em crianças : um estudo com equivalência de estímulos - Santos, Silvana Lopes dos (2017)
Questions about the possible influence of marketing on children's food choices have been topics of debate in recent years. The use of characters in advertisements and packaging is one strategy commonly used to develop positive attitudes toward brands or products. Research that used the stimulus equivalence paradigm has shown that such influence can occur through the transfer of functions. The purpose of this thesis was to verify under what conditions an abstract symbol can acquire symbolic functions of characters and influence children's food choices. Therefore, three studies were carried out. In Study 1 of this thesis, the children formed two classes of stimuli: one containing a liked character and the other a dislike character. The other members were geometric figures and abstract symbols. Three choice and preference tests were conducted where the children had to choose from two samples of the same snack, differing only by the label on the package: 1) symbol equivalent to the liked and disliked characters; 2) symbol equivalent to the disliked character and a new symbol; and 3) the symbol equivalent to the liked character and the logo a known brand. Most children chose first, and reported to like more, the snack labeled with the symbol equivalent to the liked character. They also chose, and reported to like more, the snack labeled with a new stimulus over the symbol equivalent to the disliked character. The Test 3 was inconclusive. Study 2 was similar, however, rather than the known brand, this was replaced by another new symbol in the Test 3. The equivalence tests and the food choice and preference tests were repeated after two weeks. The results of Test 1 were replicated, but the tests 2 and 3 were inconclusive. However, it was possible to verify both the maintenance of the equivalence relations and the transfer of function. In Study 3 the children formed three classes of equivalence, one of which contained a neutral figure. The preference tests were similar; however, the “neutral” symbols replaced the new symbols. The function transfer results were even more robust because all children chose and liked more the food with the symbol equivalent to the favorite character on the label. It has also been noted that children tend to choose a food with a symbol equivalent to the character, even if not attractive, when the other option is a label with a "neutral" symbol. The analysis of the profile and consumption habits of private school participants (Studies 1 and 2) and public (Study 3) pointed to some significant differences relative to food consumption, participation in purchases, hours of televisions, etc, which may have influenced in the obtained results. It is considered that the results achieved have empirically demonstrated how children can be persuaded by using attractive figures. They also brought contributions that strengthen the stimulus equivalence paradigm as a behavioral model the semantic relations and an useful methodology for the study of the attitudes and preferences.